Exploring the learner's knowledge construction and cognitive patterns of different asynchronous platforms: comparison of an online discussion forum and Facebook - Hou, Huei-Tse; Wang, Shu-Ming; Lin, Peng-Chun; Chang, Kuo-En (Innovations in education and teaching international, 2015)
The primary purpose of this study is to explore the knowledge construction behaviour and cognitive patterns involved in students' online discussion using online forum and Facebook (FB). This study employed quantitative content analysis and lag sequential analysis to examine the content and behavioural patterns of 50 students from a private university in Taiwan in their online discussion with a project-based learning activity. Results showed that FB, in contrast to online discussion forum, better facilitated students' social interaction, as they exhibited more off-topic discussion and focusing on the subject of discussion in terms of behavioural continuity. Results also showed that students were primarily sharing knowledge and involving cognitive process of 'understanding' during discussion. Nonetheless, more advanced knowledge construction behaviour and cognitive process were not observed in this study. Accordingly, this study suggests that incorporating FB in learning with adequate guidance by the instructor could be beneficial to improve students' engagement.